1960
DOI: 10.1128/jb.80.2.171-179.1960
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bacterial Urease in Experimental Pyelonephritis

Abstract: Infections of the kidney are produced by bacteria that seldom infect other organs. This fact is evident from an analysis of the relative frequency with which different bacterial species are isolated in infected urines. Studies summarized in table 1 disclosed that Escherichia coli was the most frequent cause of urinary infection and Proteus species are next. Then in diminishing order there were Aerobacter aerogenes, Klebsiella pneumoniae, paracolon organisms, Pseudomonas aeruginosa, enterococci, and Alcaligenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

1962
1962
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(46 citation statements)
references
References 7 publications
1
43
0
1
Order By: Relevance
“…Second, as noted above, bacterial attachment may facilitate invasion of the renal parenchyma. The closely packed layers of adherent bacteria seen in this study may have injured the underlying epithelial cells, either through the cytotoxic effects of a bacterial product such as urease (23,28) or indirectly, by hydrolytic enzymes released from phagocytosing leukocytes (29). Adherence may also be a prerequisite for the intracellular penetration of intact mucosal cells.…”
Section: Phenomenon Also Occurs In Humans Amar Observed Calicotubulamentioning
confidence: 77%
See 1 more Smart Citation
“…Second, as noted above, bacterial attachment may facilitate invasion of the renal parenchyma. The closely packed layers of adherent bacteria seen in this study may have injured the underlying epithelial cells, either through the cytotoxic effects of a bacterial product such as urease (23,28) or indirectly, by hydrolytic enzymes released from phagocytosing leukocytes (29). Adherence may also be a prerequisite for the intracellular penetration of intact mucosal cells.…”
Section: Phenomenon Also Occurs In Humans Amar Observed Calicotubulamentioning
confidence: 77%
“…Proteus also appeared capable of penetrating intact epithelial cells and it is possible that the organisms may have been passing through the cells in a manner similar to the mechanism whereby ShigeUa (8) or Salmonella (9) reach the intestinal submucosa. P. mirabilis may have a specific ability to parasitize renal epithelial cells as Braude and Siemienski have reported that monkey kidney epithelial cells grown in tissue culture are susceptable to intracellular colonization by P. mirabilis but not by E. coli (23). Finally, the discovery of bacteria in Bowman's space and in occasional tubular lumina suggest that bacteria may also reach the cortex as a result of calicotubular backflow.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, interest in urease is due to the association of the enzyme with human disease. There are two sites of infection, the urinary tract {Braude and Siemienski, 1960;Griffith et al, 1976;Takeuchi et al, 1980) and the gastroduodenal region (Blaser, 1992), where bacterial ureases are thought to play a significant role in pathogenesis. At both sites, it is the production of ammonia that is important for the development of disease.…”
Section: Introductionmentioning
confidence: 99%
“…If the organism is a strain of Proteus producing the enzyme urease, urea in the urine is broken down to ammonia and the pH of the urine is increased, thus favouring the precipitation of relatively insoluble crystalloids which with the foreign body as a nucleus eventually form massive urinary calculi. (The role of bacterial urease in pyelonephritis has been studied experimentally by Braude & Siemienski, 1960. ) Presumably pressure of urine due to the obstruction in the bladder spreads the infection to the kidneys via the ureters, leading to renal failure and death.…”
Section: Discussionmentioning
confidence: 99%